Enhanced Extracellular Production of Aspartyl Proteinase, a Virulence Factor, by Candida albicans Isolates following Growth in Subinhibitory Concentrations of Fluconazole - Wu, Tao (American Society for Microbiology, 2000)
We examined the production of secreted aspartyl proteinase (Sap), a putative virulence factor of Candida albicans, by a series of 17 isolates representing a single strain obtained from the oral cavity of an AIDS patient before and after the development of clinical and in vitro resistance to fluconazole. Isolates were grown in Sap-inducing yeast carbon base-bovine serum albumin medium containing 0, 0.25, 0.5, or 1 MIC of fluconazole, and cultures were sampled daily for 14 days to determine extracellular Sap activity by enzymatic degradation of bovine serum albumin. Extracellular Sap activity was significantly decreased in a dose-dependent manner for the most fluconazole-susceptible isolate (MIC, 1.0 μg/ml) and significantly increased in a dose-dependent manner for the most fluconazole-resistant isolate (MIC, >64 μg/ml). Enhanced extracellular Sap production could not be attributed to cell death or nonspecific release of Sap, because there was no reduction in the number of CFU and no significant release of enolase, a constitutive enzyme of the glycolytic pathway. Conversely, intracellular Sap concentrations were significantly increased in a dose-dependent manner in the most fluconazole-susceptible isolate and decreased in the most fluconazole-resistant isolate. Enhanced Sap production correlated with the overexpression of a gene encoding a multidrug resistance (MDR1) efflux pump occurring in these isolates. These data indicate that exposure to subinhibitory concentrations of fluconazole can result in enhanced extracellular production of Sap by isolates with the capacity to overexpress MDR1 and imply that patients infected with these isolates and subsequently treated with suboptimal doses of fluconazole may experience enhanced C. albicans virulence in vivo.